Understanding the metrics used to assess the quality of journals - Pathak, Vineet Kumar; M., Mohan Kumar (International Journal Of Community Medicine And Public Health, 2019)
Various databases offer access to thousands of academic journals. A miscellaneous picture with respect to quality, scientific influence and prestige is presented by umpteen numbers of journals present. Authors wishing to publish their research aim to publish in journals with the highest ratings and are ultimately in no man’s land.